KEEFEKTIFAN MODEL KONSEP KALIMAT DENGAN MEDIA FLASH CARD DALAM MENULIS TEKS DESKRIPTIF TENTANG PERISTIWA BUDAYA PADA KELAS 7 SMP N 1 AMBARAWA - Wijayanti, Evi (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2016)
ABSTRACT This research aimed to find out the differences of the ability of writing descriptive text about cultural event between students who learned sentence concept model using flash card and students who learned without concept sentence model without using flash card. Besides, this research also aimed to examine the effectiveness of concept sentence model using flash card media in writing descriptive text about cultural event for seven graders. The research design used in this study was quasi experimental design which was Nonequivalent Control Group Design. The population of this study was the seven graders of SMP Negeri 1 Ambarawa. The sampling it was obtained VII C as the experimental group and VII A as the control group. The conclusions of this study were as follows: First, there were significant difference of the ability in writing descriptive text between students who learned sentence concept model using flash card media and students who learned concept sentence model without using flash card media. Second, concept sentence model using flash card media was effective for teaching writing descriptive text about cultural event. Keyword :effectiveness, concept sentence model, flash card media, writing descriptive tect. ABSTRAK Penelitian ini bertujuan untuk mengetahui perbedaan kemampuan menulis teks deskriptif peristiwa budaya antara siswa yang mengikuti pembelajaran dengan menggunakan model konsep kalimat dan media flash card dan siswa yang mengikuti pembelajaran tanpa menggunakan model konsep kalimat dan media flash card. Selain itu, penelitian ini juga bertujuan untuk menguji keefektifan model pembelajaran konsep kalimat dan media flash card dalam pembelajaran menulis teks deskriptif tentang peristiwa budaya. Penelitian ini merupakan penelitian Quasi Experimental Design dengan pola Nonequivalent control group design. Populasi dalam penelitian ini adalah siswa kelas VII SMP Negeri 1 Ambarawa, dengan sampel kelas VII C sebagai kelompok eksperimen dan kelas VII A sevagai kelompok kontrol. Kesimpulan dari penelitian ini adalah, pertama terdapat perbedaan kemampuan menulis teks deskriptif yang signifikan antara siswa dari kelompok kontrol dan kelompok eksperimen. Kedua, model pembelajaran konsep kalimat dan media flash card efektif digunakan dalam pembelajaran menulis teks deskriptif tentang peristiwa budaya. Kata kunci : keefektifan, model konsep kalimat, media flash card, menulis teks deskriptif